A community based study on e-waste disposal in Srinagar, Uttarakhand: assessment of awareness and practices - Nath, Bhola; Kumari, Ranjeeta; Gupta, Valendu; Vaswani, N. D.; Lekhwani, Seema (International Journal Of Community Medicine And Public Health, 2018)
Background: ‘E-waste’ is waste electrical and electronic equipment (EE) which are intended to be discarded. Improper disposal leads to hazardous effects on health and environment. Awareness about e-waste is important for all those using EE. Methods: It was a community based cross sectional study among consumers of EE and scrap dealers in Srinagar city, of Pauri district in Garhwal division of Uttarakhand. Information was collected on knowledge about e-waste, its types and disposal practices. Results: Only 6.7% respondents heard the term E-waste. 77% of the respondents didn’t know about the ways of disposing the e-waste and 45.7% were totally unaware of hazardous effects of improper disposal. Knowledge among scrap dealers was altogether absent. Conclusions: Awareness on various aspects of E-waste was found to be poor among respondents and totally absent among scrap dealers.